2016
DOI: 10.3390/ijms17091399
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Distribution and Role of Aquaporin Water Channels in Human and Animal Stomach and Intestines

Abstract: Stomach and intestines are involved in the secretion of gastrointestinal fluids and the absorption of nutrients and fluids, which ensure normal gut functions. Aquaporin water channels (AQPs) represent a major transcellular route for water transport in the gastrointestinal tract. Until now, at least 11 AQPs (AQP1–11) have been found to be present in the stomach, small and large intestines. These AQPs are distributed in different cell types in the stomach and intestines, including gastric epithelial cells, gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 116 publications
(247 reference statements)
3
86
0
10
Order By: Relevance
“…2E). Indeed, the CD69 + CD274 + population lacks Chga , Cck , Ghrl , and other abundant EE transcripts but selectively expresses known goblet-cell genes (Pelaseyed et al, 2014; Zhu et al, 2016) (Figs. 2E–F and S3D).…”
Section: Resultsmentioning
confidence: 99%
“…2E). Indeed, the CD69 + CD274 + population lacks Chga , Cck , Ghrl , and other abundant EE transcripts but selectively expresses known goblet-cell genes (Pelaseyed et al, 2014; Zhu et al, 2016) (Figs. 2E–F and S3D).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from serving as the site of nutrient uptake and osmoregulation, the intestine functions as a critical defense barrier to the external environment (Grosell 2011). The intestinal fluid balance in the fish as well as mammalian has been indicated to be cooperated by various factors, including hormones, intestinal contents, inflammatory factors, and feeding (Rombout et al 2011;Zhu et al 2016). Thus, the bacterial challenge may either directly or indirectly linked to unfavorable change of water balance in the intestine in the pathophysiological stress.…”
Section: Discussionmentioning
confidence: 99%
“…AQPs are a family of transmembrane transporter proteins and are subdivided into 3 groups based on their functional characteristics: 1) orthodox AQPs (AQP1, 2, 4, and 5), which are selectively permeable for water; 2) aquaglyceroporins (AQP3, 7, 9, and 10), which are permeable to glycerol, urea, and other small solutes, in addition to water; and 3) unorthodox AQPs (AQP6, 8, 11, and 12), with peculiar intracellular localization and functions (for review see Matsuzaki et al 30). We focused on AQP3 because of its localization on the membranes of gastric and intestinal cells (14) and the fact that cell AQP3 knockdown and mouse knockout models resulted in reduced migration, lamellipodia formation, and increased sensitivity to injury (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…In a further series of studies, we examined whether any effects found were mediated through TFF actions on AQP levels, with particular focus on AQP3. That focus was based on the findings that AQP3 is produced in surface enterocytes of both the stomach and intestine (13) and using a variety of models, including knockdown and knockout models, has been shown to be important in maintaining gut integrity, increasing cell migration, and stimulating repair (14, 15).…”
mentioning
confidence: 99%